2013
DOI: 10.2478/intag-2013-0004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the soil water content on Jatropha seedlings in a tropical climate

Abstract: A b s t r a c t. The purpose of this study was to evaluate growth, chlorophyll content, and photosynthesis in Jatropha at different levels of soil moisture. Plants were cultivated in containers and the treatments of the soil water content evaluated were: 0% (without watering), 20, 40, 60, and 80% soil water content. Plant height was statistically similar for all treatments, but the number of leaves differed significantly. Total dry matter and chlorophyll at 40, 60, and 80% soil water content were statistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…This result is in good agreement with that reported by Pérez -Vazquez et al (2013), who found that total dry matter at 0.6, 0.4, and 0.2-DI, were statistically similar, but different from 0.9 and 0.80-DI. On the other hand, reduction in the same vegetative characters under 0.6-DI (0.4 field capacity) was agreed to somewhat with that obtained by Jayasundara et al (2014).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This result is in good agreement with that reported by Pérez -Vazquez et al (2013), who found that total dry matter at 0.6, 0.4, and 0.2-DI, were statistically similar, but different from 0.9 and 0.80-DI. On the other hand, reduction in the same vegetative characters under 0.6-DI (0.4 field capacity) was agreed to somewhat with that obtained by Jayasundara et al (2014).…”
Section: Resultssupporting
confidence: 93%
“…Effect of soil moisture content on growth and yield in Jatropha was covered in some studies, Jayasundara et al (2014) found that decreasing soil moisture content at early growth stage up to 50 -60% (depletion level) was negatively affected the vegetative plant growth. On the other hand, Pérez-Vazquez et al (2013) found that total dry matter and chlorophyll at 40, 60 and 80% soil water content (SWC) were statistically similar. In arid regions where irrigation is the most limited factor for crop production, it is imperative to have complete information for economic production of Jatropha for maximum utilization.…”
Section: Introductionmentioning
confidence: 96%
“…Some variables that are correlated with plant height and stem diameter are the total dry matter and leaf area index [ 42 ]. In this regard, Schwerz et al [ 21 ], when intercropping S .…”
Section: Discussionmentioning
confidence: 99%
“…Jatropha , with thicker stems and lower slender indexes, reflects a strong adaptation to dry environments, storing resources at the base of its stem [34]. It is important to remark, here, that this subtropical site has a pronounced dry season that can last up to five or six months; thus, native trees and shrubs, like Jatropha , have developed morphological adaptations to deal with this dry period [35]. Moringa represented a different strategy to cope with arid places because it developed the thinnest stem (Figure 1), but also 11% higher elongation rates than Jatropha .…”
Section: Discussionmentioning
confidence: 99%